A methodology for evaluating capability, effort and ease of implementation in modular web content management systems - Ramnath, Aveer (My University, 2017)
Modular web content management systems (WCMS) are widely adopted software plat- forms that facilitate the creation of web applications through a process of con guration and assembly of add-on modules. Although WCMSs have been used in a variety of ap- plication domains (e-commerce, news) no clear guidance as to when it is suitable to use a WCMS could be found. This work proposes a methodology to evaluate the suitability of a WCMS in a particular context. This is done by evaluating the suitability indicators (capability, e ort and ease of implementation) for a given WCMS application. The met- hodology evaluates each indicator per application requirement. Capability is evaluated on a Yes/No basis. E ort is evaluated using e ort level, a relative indicator of e ort. E ort levels are de ned in terms of increasing e ort, varying from 0 (feature present in the product) through to 5 (feature requires a custom module to be written). Ease of implementation is evaluated using a qualitative measure (easy, moderate or di cult) of the implementation di culty. The methodology has been successfully validated through the development and evaluation of a web application for a school within a university faculty. In this instance the WCMS capability was evaluated at 100%, as all require- ments could be implemented. The e ort level analysis showed 16% of requirements were present by default in the core product, 22% required some con guration of the core pro- duct, 32% required a single add-on module to be installed, and 30% required multiple add-on modules to be installed. The ease of implementation analysis showed that 86% of requirements were easy, 7% moderate and 7% di cult. The analysis is presented in order to demonstrate the operation of the methodology. Further data would be nee- ded to extrapolate general trends. With repeated use of the methodology in various contexts, it would be possible to build up a useful reference for those considering the use of a WCMS. In addition, this data would permit analysis of overall strengths and weaknesses of a particular WCMS.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science in Engineering in the Faculty of Engineering and the Built Environment School of Electrical and Information Engineering August 2017
Keywords: Web sites--Evaluation; Web site development; Web sites--Management; World Wide Web; Software engineering